Ameliorating Iron Overload in Intestinal Tissue of Adult Male Rats: Quercetin vs Deferoxamine - Arwa A. El-Sheikh; Shimaa Hamed Ameen; Samaa Salah AbdEl-Fatah (Journal of Toxicology)
Objective. The aim of our study is to compare the role of the new natural alternative (Quercetin) with the current iron-chelation therapy (Deferoxamine (DFO)) in the effect of iron overload on small intestinal tissues and to investigate the possible underlying molecular mechanisms of such toxicity. Methods. Forty-two adult male albino rats were divided into six groups: control groups, DFO, Quercetin, iron overload, iron overload+DFO, and iron overload+Quercetin groups. Animals received daily intraperitoneal injection of Deferoxamine (125 mg /kg), Quercetin (10 mg/kg), and ferric dextran (200 mg/kg) for 2 weeks. Results. Iron overloaded group showed significant increase in serum iron, total iron binding capacity (TIBC), transferrin saturation percentage (TS %) hepcidin (HEPC), serum ferritin, nontransferrin bound iron (NTBI), and small intestinal tissues iron levels. Iron overload significantly increased the serum oxidative stress indicator (MDA) and reduced serum total antioxidant capacity (TAC). On the other hand, iron overload increased IL6 and reduced IL10 in small intestinal tissues reflecting inflammatory condition and increased caspase 3 reactivity indicating apoptosis and increased iNOs expressing cell indicting oxidative stress especially in ileum. In addition, it induced small intestinal tissues pathological alterations. The treatment with Quercetin showed nonsignificant differences as compared to treatment with DFO that chelated the serum and tissue iron and improved the oxidative stress and reduced tissue IL6 and increased IL10 and decreased caspase 3 and iNOs expressing cells in small intestinal tissues. Moreover, it ameliorated the iron overload induced pathological alterations. Conclusion. Our study showed the potential role of Quercetin as iron chelator like DFO in case of iron overload induced small intestinal toxicity in adult rats because of its serum and tissue iron chelation, improvement of serum, and small intestinal oxidative stress, ameliorating iron induced intestinal inflammation, apoptosis, and histopathological alterations.